2015
DOI: 10.1002/crat.201400484
|View full text |Cite
|
Sign up to set email alerts
|

Unique morphologies of zinc oxide synthesized by thermal decomposition and co‐precipitation routes: Ultraviolet absorption and luminescence characteristics

Abstract: Two facile and efficient methods, to synthesize zinc oxide (ZnO) particles with different morphologies, have been reported here. Thermal decomposition route yielded micron sized irregular shaped ZnO particles. While co‐precipitation method rendered transparent flakes which then transformed to hexagonal discs with relatively more uniform size and shape. These hexagonal discs were further converted to the cone type morphology when hexamethylenetetramine was added in the precursor solution. However, spherical typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…The properties of zinc oxides are related to their morphology. Morphologically diverse zinc oxide structures can be produced by various synthetic methods, such as vapor deposition, precipitation, sol–gel synthesis, hydrothermal synthesis, etc. Our hypothesis is that the morphologic diversity will be reduced as the particle goes from larger nanoparticles to USNPs, despite the local geometry becoming more diverse. A USNP morphology can possibly grow into several different regular nanoparticle morphologies via different growth patterns.…”
Section: Introductionmentioning
confidence: 99%
“…The properties of zinc oxides are related to their morphology. Morphologically diverse zinc oxide structures can be produced by various synthetic methods, such as vapor deposition, precipitation, sol–gel synthesis, hydrothermal synthesis, etc. Our hypothesis is that the morphologic diversity will be reduced as the particle goes from larger nanoparticles to USNPs, despite the local geometry becoming more diverse. A USNP morphology can possibly grow into several different regular nanoparticle morphologies via different growth patterns.…”
Section: Introductionmentioning
confidence: 99%
“…The slight increase in the intensities of these peaks can attributed to addition of zinc compound and heat treatment enhanced the crystallinity of PVC nanofiber. Since corresponding ZnO peaks are not presented at the XRD patterns [18,19], it is very difficult to mention that zinc nitrate was transformed to well crystallize zinc oxide structure in this study. In the literature, it was reported that when ZnO was added to PVC, UV absorption increased and transmittance was decreased [7,8].…”
Section: Sayfa 121mentioning
confidence: 91%
“…CH stretching at 2914 cm -1 , CH-rocking at 1251 cm -1 and CH 2 deformation at 1330 cm -1 were observed [16,17]. The presence of NO 3 −1 increases the peak intensities between 1220-1370 cm -1 [18]. After NaOH and heat treatment these peak intensities decreased ( Figure 5B, 5C) since some NO 3 has been removed as a result of NaOH treatment and a following rinsing.…”
Section: Sayfa 121mentioning
confidence: 99%
“…Some of its applications in different fields of electronics include the devices used in surface acoustic wave, sensors, UV lasers, field emitters and cells [3]. It has wide band gap of 3.37 eV and high bond strength of 60 meV at ambient conditions [4]. So ZnO is a promising candidate as a low-cost porous semiconductor material and has been investigated as photo anode in dye-sensitized solar cells (DSSCs) [5][6].…”
Section: Introductionmentioning
confidence: 99%